2022
DOI: 10.1103/physreva.105.063310
|View full text |Cite
|
Sign up to set email alerts
|

Three-body problem in a multiband Hubbard model

Abstract: We first apply functional-integral approach to a multiband Hubbard model near the critical pairing temperature, and derive a generic effective action that is quartic in the fluctuations of the pairing order parameter. Then we consider time-reversal-symmetric systems with uniform (i.e., at both low-momentum and low-frequency) pairing fluctuations in a unit cell, and derive the corresponding time-dependent Ginzburg-Landau (TDGL) equation. In addition to the conventional intraband contribution that depends on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…However, since Eq. ( 8) is formally identical to that of the two-fermion case, we skip their detailed analysis here and refer the reader to the recent literature [2,3]. Just like the fermion problem, it can be shown that, by representing Eq.…”
Section: B Two-body Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…However, since Eq. ( 8) is formally identical to that of the two-fermion case, we skip their detailed analysis here and refer the reader to the recent literature [2,3]. Just like the fermion problem, it can be shown that, by representing Eq.…”
Section: B Two-body Spectrummentioning
confidence: 99%
“…The three-body bound states can be determined by the integral Eq. ( 9) through an iterative procedure [3]. Instead, in order to reveal the full three-body spectrum, where we recast Eq.…”
Section: Three-body Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…The Hubbard model provides a theoretical framework to study multiband systems, and serves as a protoypical model for studying electron-electron interactions and electron itinerancy [16][17][18]. The Hubbard model incorporates a tight-binding term to describe electron hopping between lattice sites and a local Coulomb interaction term to account for electron-electron interactions.…”
Section: Introductionmentioning
confidence: 99%